2007
DOI: 10.1016/j.anireprosci.2006.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and morphometric characterization of buffalo (Bubalus bubalis) ovarian preantral follicles

Abstract: The main objective of the present study was to characterize buffalo preantral ovarian follicles. Parts of ovarian cortex, collected from postpubertal buffalo females that were having estrous cycles at regular intervals, were selected under stereomicroscopy and processed for optic and transmission electron microscopy. Primordial follicles were characterized as an oocyte encircled by one layer of flattened cells. The buffalo primordial follicle has a mean diameter of 35 microm and the oocyte diameter is 24.9 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
5
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 20 publications
6
38
5
4
Order By: Relevance
“…In the present study, the average diameter measurements of primordial, primary, and secondary follicles and of oocytes were lower than some of those previously reported [6], although in agreement with those reported in adult cattle [41,42] and adult buffaloes [43]. Though the number of follicular cells in primordial, primary, and secondary follicles was similar to those previously reported in adult cattle [41], it differed from reports in adult buffaloes [43].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In the present study, the average diameter measurements of primordial, primary, and secondary follicles and of oocytes were lower than some of those previously reported [6], although in agreement with those reported in adult cattle [41,42] and adult buffaloes [43]. Though the number of follicular cells in primordial, primary, and secondary follicles was similar to those previously reported in adult cattle [41], it differed from reports in adult buffaloes [43].…”
Section: Discussioncontrasting
confidence: 52%
“…Though the number of follicular cells in primordial, primary, and secondary follicles was similar to those previously reported in adult cattle [41], it differed from reports in adult buffaloes [43].…”
Section: Discussioncontrasting
confidence: 40%
“…In non-domestic cats, the endoplasmic reticulum is not well developed and Golgi complexes are rarely seen [59]. In the ooplasm of buffaloes, a delimited region with a well-developed smooth endoplasmic reticulum is observed [45]. In yaks [52] and pigs [49], polyribosomes are seen on the surface of the rough endoplasmic reticulum and distributed throughout the ooplasm.…”
Section: Introductionmentioning
confidence: 99%
“…When we compared our findings with the results of other species we observed that the mean follicular diameter was higher in primordial follicles, unilaminar and multilaminar primary follicles (45.13 μm, 70.35 μm and 127.60 μm) than diameters obtained in other species as in pre-pubertal gilts (33.8 μm, 40.4 μm and 84.5 μm) [13] and young women (< 13 years) (39 μm and 44.1 μm) [17]; the mean follicular diameter of older queens was higher in primordial and unilaminar primary follicles (43.24 μm and 68.11 μm, respectively) compared to post-pubertal female buffaloes (7 -10 years) (35 μm and 41.8 μm, respectively) [10]; the mean oocyte diameter in young animals was higher in primordial, unilaminar and multilaminar primary follicles (40.55 μm, 47.97 μm and 62.35 μm, respectively) when comparing with pre-pubertal gilts (26 μm, 27.3 μm and 39.1 μm) [13] and women (< 13 years) with values for primordial and unilaminar primary follicles (34.3 μm and 41 μm, respectively) [17].…”
Section: Discussionmentioning
confidence: 99%